Polymer coated urea does not improve nitrogen use efficiency above urea in ratoon sugarcane crops in the wet subtropics - Terry J. Rose; Josh Rust; Lukas Van Zwieten; Michael T. Rose (Nutrient Cycling in Agroecosystems, 2025)

Ameliorating alkaline dispersive subsoils with organic amendments: Are productivity responses due to nutrition or improved soil structure? - Shihab Uddin; Stephanie Watts Williams; Naveed Aslam; Yunying Fang; Shahnaj Parvin; Josh Rust; Lukas Van Zwieten; Roger Armstrong; Ehsan Tavakkoli (Plant and Soil, 2022)
Background and aims Alkaline dispersive subsoils are characterised by multiple physicochemical constraints that limit plant water and nutrient acquisition. Subsoil amelioration through organic amendments (OAs) requires significant financial investment. Whereas large yield responses can result following amelioration, sometimes small or even negative yield responses can occur, resulting in a significant net financial loss for the farmer. For farmers to feel confident in investing in subsoil amelioration better prediction of the likely yield improvement is required and to achieve this an understanding of the underlying mechanisms such as nutritional and non-nutritional drivers, and the longevity of benefits are required. Our study aimed to ascertain the drivers of yield improvements from subsoil amelioration with OAs. Methods In a controlled environment, wheat ( Triticum aestivum L. cv. Scepter) plants were grown until maturity in a Solonetz amended with (i) poultry litter (PL; 20 t ha −1 ), and (ii) NPKS nutrients and (iii) model organic carbon (MOC) with equivalent amounts of nutrients and total carbon contained in the PL, and (iv) NPKS + MOC. Control (no amendments) and gypsum (5 t ha −1 ) were included as district practices. Before planting, amendments were applied as a vertical band at 20 – 40 cm depth and pre-incubated. Plant biomass, grain yield, root biomass, and physicochemical properties of the soil associated with the amendment band were quantified at harvest. Results Compared to the control, wheat grain yield was increased by 30% for PL, 43% for NPKS + MOC, and 61% for NPKS, but no differences in yield were detected for MOC or gypsum. The lower yield increase by PL than NPKS with or without MOC was likely due to the readily available form of plant nutrients in the inorganic fertilisers vs slower mineralisation of nutrients from the OAs. Improvement in soil physicochemical properties following amelioration of alkaline dispersive subsoil resulted in better root proliferation and subsoil water use. Grain yield showed a positive correlation with root biomass in the subsoil layers. Conclusions In the short-term (one crop cycle), organic amendments improved soil’s non-nutritional physical and chemical properties but had no additional nutritional effect on wheat grain yield compared to inorganic fertiliser application. Longer-term studies are needed to determine the legacy effect of the nutritional contribution in conjunction with the improvement of soil structure from the OAs in alkaline dispersive subsoils.

Enhanced biological N2 fixation and yield of faba bean (Vicia faba L.) in an acid soil following biochar addition: dissection of causal mechanisms - Lukas Van Zwieten; Terry Rose; David Herridge; Stephen Kimber; Josh Rust; Annette Cowie; Stephen Morris (Plant and Soil, 2015)